LIMITATIONS OF THE GDP AS A MEASURE OF PROGRESS AND WELL-BEING (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
The subject of this paper is the gross domestic product that has become a universal measure of progress and well-being. However, its usage for this purpose is inadequate, inappropriate and wrong since this economic measure does not reflect anything more than productivity. Moreover, it was never designed to be more than just a monetary measure and, besides that, it has a lot of limitations and weaknesses that are not sufficiently presented to the general public or in academic papers. In this paper the limitations of the GDP are shown by defining and describing its historical aspects Moreover, the SWOT analysis is used to emphasize the weaknesses and restrictions of this monetary measure. Structured critiques of the gross domestic product make way for other measures of progress and well-being to be recognized and used in a more comprehensive way.Keywords: GDP, GDP limitations, progress, well-being, alternative measures